Spatio-Temporal Variations in Community Size Structure of Arctic Protist Plankton in the Fram Strait - Lampe, Vanessa; Nöthig, Eva-Maria; Schartau, Markus (Frontiers in Marine Science, 2021)
3 The Arctic Ocean is subject to severe environmental changes, including the massive decline 4 in sea ice due to continuous warming in many regions. Along with these changes, the Arctic 5 Ocean’s ecosystem is affected on various scales. The pelagic microbial food web of the Arctic is 6 of particular interest, because it determines mass transfer to higher trophic levels. In this regard, 7 variations in the size structure of the microbial community reflect changes in size-dependent 8 bottom-up and top-down processes. Here we present analyses of microscopic data that resolve 9 details on composition and cell size of unicellular plankton, based on samples collected between 10 2016 and 2018 in the Fram Strait. Using the Kernel Density Estimation method, we derived 11 continuous size spectra (from 1 μm to ≈ 200 μm Equivalent Spherical Diameter, ESD) of cell 12 abundance and biovolume. Specific size intervals (3–4, 8–10, 25–40, and 70–100μm ESD) 13 indicate size-selective predation as well as omnivory. In-between size ranges include loopholes 14 with elevated cell abundance. By considering remote sensing data we could discriminate between 15 polar Arctic- and Atlantic water within the Fram Strait and could relate our size spectra to 16 the seasonal change in chlorophyll-a concentration. Our size spectra disclose the decline in 17 total biovolume from summer to autumn. In October the phytoplankton biovolume size-spectra 18 reveal a clear relative shift towards larger cell sizes (> 30 μm). Our analysis highlights details in 19 size spectra that may help refining allometric relationships and predator-prey dependencies for 20 size-based plankton ecosystem model applications.